2003
DOI: 10.1103/physreve.68.061509
|View full text |Cite
|
Sign up to set email alerts
|

Fractal patterns, cluster dynamics, and elastic properties of magnetorheological suspensions

Abstract: We study pattern formation and the aggregation processes in magnetorheological suspensions in the presence of a static magnetic field, and some of their associated physical properties. In particular, we analyze the elastic modes as a function of the intensity of the applied field and for several particle concentrations. We observe that the clusters formed in these systems have multifractal characteristics, which are the result of three well defined stages of the aggregation process. In these stages three gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…By SAXS experiments, we can analyze the first-generation clusters [21], by AFM the secondgeneration ones, and finally SEM reveals a third stage of these aggregation patterns. The fiber-like first generation clusters aggregate to form spherical secondgeneration ones, and in the third-aggregation process, second-generation clusters, at a large scale, aggregate and rearrange to form more complex structures.…”
Section: Second-and Third-generation Structural Parametersmentioning
confidence: 99%
“…By SAXS experiments, we can analyze the first-generation clusters [21], by AFM the secondgeneration ones, and finally SEM reveals a third stage of these aggregation patterns. The fiber-like first generation clusters aggregate to form spherical secondgeneration ones, and in the third-aggregation process, second-generation clusters, at a large scale, aggregate and rearrange to form more complex structures.…”
Section: Second-and Third-generation Structural Parametersmentioning
confidence: 99%
“…Blair and Kudrolli [5] found that for small values of parameter Γ, T g depends linearly with Γ. The concentration, φ, is defined as the ratio between the number of paramagnetic particles n 1 and the total number of the particles n 2 .…”
Section: Experimental Procedures and Setupsmentioning
confidence: 99%
“…In this analysis, the mass fractal dimension and the radial distribution function of the cluster structure were measured on digital pictures. The method used in this paper to measure the mass fractal dimension is a variation of the standard box counting method, adapted to explore radial and angular correlations in systems affected by potentials with radial or axial symmetries [5,6]. In this method, the mass fractal dimension is defined by the power law: M ∝ r D where M is the average mass contained in a circle of gyration radius r. This mass is measured in an ensemble to properly extract the information of the correlations.…”
Section: Static Structurementioning
confidence: 99%
See 1 more Smart Citation
“…We have studied pattern formation in MRS formed by micrometric iron oxide particles dispersed in silicone oil, in the presence of an external field. We have found that the resulting structure exhibits three aggregation stages, which can be well characterized by the behaviour of their measured mass fractal dimension [2]. In this work, we calculate and discuss the mass radial distribution, this function shows another aspect of the different regimes of mass scaling, and could provide additional elements to describe the hierarchical structure of the MRS.…”
mentioning
confidence: 99%